Influence of Instructional Supervisory Qualities on Science Teachers’ Teaching Competency - Ismail, Mohd Zaid; Zanaton Iksan, Azlin Norhaini Mansor, (Opción)
This study was done quantitatively using a questionnaire survey on 311 science teachers in Terengganu, Malaysia. The collected data were analyzed using SPSS version 20.0 and involved descriptive and inferential statistical analysis. The descriptive analysis revealed that principals’ instructional supervisory qualities and science teachers’ teaching competency were at high levels. The inferential analysis from the t-test found no significant difference in the teaching competency of different gender and schools’ location. One-way ANOVA tests also showed that there was no significant difference in the teaching competency of science teachers with different experience levels. Further analysis using Pearson’s Correlation showed a significant relationship between the instructional supervisory qualities and science teachers’ teaching competency